Pengembangan website berbasis Google Site sebagai media pembelajaran blended learning Karawitan melalui fitur interaktif - Jatilinuar, Setya Rahdiyatmi Kurnia; Widyastuti, Ipuk (Universitas Negeri Yogyakarta, 2023)
The development of technology that presents a 'new era', namely the digital era, is one of the aspects driving blended learning, especially in karawitan practice courses. Of course, this change in learning methods raises various kinds of efforts and new challenges that must be faced, one of which is in choosing appropriate learning methods and media. This research is an effort to develop the use of blended learning media by utilizing google sites. Google site was developed by referring to smartphone-based learning media to be 'user-friendly', meaning that it can be easily used or accessed by students and lecturers. Google site is an alternative to online learning media, especially in practical lectures because it is 'user-friendly' (flexible, easy to access/operate, smartphone-based), has adequate features, has an attractive-systematic design, and does not require large costs (free access). The method used in this study is a qualitative method with data collection techniques through observation, literature studies, and questionnaires. The type of data is quantitative data that is processed using survey, comparative, and descriptive methods. The population of this study are students and lecturers of the Karawitan Department of ISI Yogyakarta. This research uses symbol system theory, e-learning, and blended learning in the development of google sites. The results of this study are in the form of blanded learning media using google sites that have been developed by adding interactive features.